Learners’ Perceptions on Peer Assessment in Team-Based Learning Classroom - Chorrojprasert, Linchong (LEARN Journal: Language Education and Acquisition Research Network, 2021)
Focusing on the perceptions of learners on their peer assessment experiences, this study – a case study in nature – was conducted with mixed methods approach with the aim to shed light on how peer assessment, a prominent characteristic of team-based learning classroom, could enhance the learners’ performance and learning skills, in particular the soft skills deemed most beneficial and essential in most professions. Data collection instruments employed included a survey questionnaire and a focus group session. Participants in the study included 18 graduate students of mixed nationalities in an English Language Teaching (ELT) required course. Findings from the study confirmed most of the proffered benefits of peer assessment on learners’ improvement of knowledge and skills, and further raised some issues related to individual constraints in assessment and class preparation. Furthermore, recommendations for further study and instructional implications were discussed to provide guidance for those who share similar teaching contexts and are keen to embrace these teaching challenges.